Case Report: Papillary renal cell carcinoma complicated by ipsilateral renal tuberculosis - Tian, Zhong; Zhu, Cheng; Yang, Tingting; Chen, Shicheng; He, Zhongcong; Han, Guang; Chen, Zhouhui; Zhang, Neng; Yu, Bo; Fu, Ni (Frontiers in Medicine, 2025)
Papillary renal cell carcinoma (PRCC) complicated by ipsilateral renal tuberculosis (TB) represents an exceptionally rare and complex clinical condition. Renal TB is the most common form of urogenital TB, while PRCC is the most prevalent histological subtype of non-clear cell renal cell carcinoma (RCC). In this study, we present the first reported case of PRCC complicated by ipsilateral renal TB, where the patient exhibited low back pain without hematuria. Initial imaging studies indicated a space-occupying lesion in the left kidney, raising suspicion of renal tumors. Subsequent postoperative pathology, immunohistochemical staining, and tuberculosis PCR results confirmed the diagnosis of PRCC complicated by ipsilateral renal TB.